Application of the Hartmann–Tran profile to analysis of H2O spectra. (October 2015) - Lisak, D.; Cygan, A.; Bermejo, D.; Domenech, J.L.; Hodges, J.T.; Tran, H.
Abstract: The Hartmann–Tran profile (HTP), which has been recently recommended as a new standard in spectroscopic databases, is used to analyze spectra of several lines of H2 O diluted in N2, SF6, and in pure H2 O. This profile accounts for various mechanisms affecting the line-shape and can be easily computed in terms of combinations of the complex Voigt profile. A multi-spectrum fitting procedure is implemented to simultaneously analyze spectra of H2 O transitions acquired at different pressures. Multi-spectrum fitting of the HTP to a theoretical model confirms that this profile provides an accurate description of H2 O line-shapes in terms of residuals and accuracy of fitted parameters. This profile and its limiting cases are also fit to measured spectra for three H2 O lines in different vibrational bands. The results show that it is possible to obtain accurate HTP line-shape parameters when measured spectra have a sufficiently high signal-to-noise ratio and span a broad range of collisional-to-Doppler line widths. Systematic errors in the line area and differences in retrieved line-shape parameters caused by the overly simplistic line-shape models are quantified. Also limitations of the quadratic speed-dependence model used in the HTP are demonstrated in the case of an SF6 broadened H2 O line, which leads to a strongly asymmetric line-shape. Abstract : Highlights: Hartmann–Tran profile (HTP) for H2 O spectral lines. Requirements for experimental data to retrieve HTP parameters. Systematic errors in line intensity and line-shape parameters vs. fitted profile.